2018
DOI: 10.1155/2018/2581031
|View full text |Cite
|
Sign up to set email alerts
|

SYKT Alleviates Doxorubicin‐Induced Cardiotoxicity via Modulating ROS‐Mediated p53 and MAPK Signal Pathways

Abstract: Backgrounds. Doxorubicin (DOX) is an effective therapeutic drug for malignant tumors; however, its clinical applications were limited by its side effects, especially the cardiotoxicity caused by ROS-mediated p53 and MAPK signal pathways' activation-induced cell apoptosis. Sanyang Xuedai mixture (SYKT) has been reported as an antioxidant agent and attenuated DOX-induced cardiotoxicity by targeting ROS-mediated apoptosis, but the mechanisms are still not fully delineated. Objective. This study aimed at investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…More reinforcement came from positive expression of p53 in these cells with significant increase in their number versus other groups. This finding was similarly reported in a prior study [41] .…”
Section: Discussionsupporting
confidence: 91%
“…More reinforcement came from positive expression of p53 in these cells with significant increase in their number versus other groups. This finding was similarly reported in a prior study [41] .…”
Section: Discussionsupporting
confidence: 91%
“…Recently, this injection is reported to restore doxorubicin-induced cardiotoxicity in H9c2 cells by improving energy metabolism and reducing oxidative stress (Yi et al, 2018 ). San-Yang-Xue-Dai mixture alleviates doxorubicin-induced cardiotoxicity and apoptosis by inhibiting p53 and MAPK signaling activation (Chen et al, 2018 ). Fermented Cordyceps sinensis is reported to attenuate doxorubicin-induced cardiotoxicity by inhibiting myocardial hypertrophy and myocardial damage, regulating systolic function, and antioxidant enzyme system and improving cardiac energy metabolism (Wu et al, 2018 ).…”
Section: Attenuation Of Cardiotoxicity Mainly By Balancing Energy Metmentioning
confidence: 99%
“…Previous studies have found that DOX-induced cardiotoxicity involves the production of reactive oxygen species (ROS) (Xu et al, 2001; Menna et al, 2012; He et al, 2018), mitochondrial dysfunction (Dolinsky, 2017; Xia et al, 2017; Gorini and De Angelis, 2018; Govender et al, 2018; He et al, 2018; Liu et al, 2018), and apoptosis (Wang et al, 2014; Mantawy et al, 2017; Chen et al, 2018; Tang et al, 2018), although the underlying mechanisms are unknown. Most evidence indicate that the major mechanism of DOX-induced cardiotoxicity involves ROS production (Xu et al, 2001; Menna et al, 2012; He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%